2020
DOI: 10.1002/pld3.281
|View full text |Cite
|
Sign up to set email alerts
|

A sorghum gigantea mutant attenuates florigen gene expression and delays flowering time

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
2
12
1
Order By: Relevance
“…guttatus , an obligate long‐day plant, in part through natural variation in critical photoperiod (Kooyers et al, 2015). Thus, consistent with its well described and conserved role in photoperiodic flowering (Abdul‐Awal et al, 2020; Bendix et al, 2013; Fowler et al, 1999; Hayama et al, 2003; Hecht et al, 2007; Park et al, 1999; Sawa & Kay, 2011), natural variation in GI expression or protein function could relate to the elevational cline previously described for this component of flowering time regulation (Kooyers et al, 2015). Several studies in trees have also described nonsynonymous polymorphisms in GI homologues associated with phenology or environmental clines (Chen et al, 2014; Holliday et al, 2010; Keller et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…guttatus , an obligate long‐day plant, in part through natural variation in critical photoperiod (Kooyers et al, 2015). Thus, consistent with its well described and conserved role in photoperiodic flowering (Abdul‐Awal et al, 2020; Bendix et al, 2013; Fowler et al, 1999; Hayama et al, 2003; Hecht et al, 2007; Park et al, 1999; Sawa & Kay, 2011), natural variation in GI expression or protein function could relate to the elevational cline previously described for this component of flowering time regulation (Kooyers et al, 2015). Several studies in trees have also described nonsynonymous polymorphisms in GI homologues associated with phenology or environmental clines (Chen et al, 2014; Holliday et al, 2010; Keller et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…Mutation of FLD in Arabidopsis (He et al, 2003) and RNA interference of its homolog in rice (Shibaya et al, 2016) delays flowering. The flowering genes: CONSTITUTIVE PHOTOMORPHOGENIC 1 (ScCOP1) (Tanaka et al, 2011), CYCLING DOF FACTOR1 (ScCDF1) (Higgins et al, 2010), SHORT VEGETATIVE (ScSVP-1 and -3) (Higgins et al, 2010), SUPPRESSOR OF CONSTANS OVEREXPRESSION 1 (ScSOC1) (Higgins et al, 2010), FLOWERING LOCUS T (ScFT) (Abdul-Awal et al, 2020) and APETALA (ScAP1) (Preston & Kellogg, 2006) peak on average 2 h earlier in 4 mo sugarcane leaves, except for ScSVP-2 (Figs 2e,f, S6).…”
Section: Resultsmentioning
confidence: 99%
“…SbGI was recently shown to be involved in photoperiodic flowering time in sorghum (Abdul-Awal et al, 2020), which is a conserved function. In Arabidopsis, GI has also been implicated in drought escape through regulation of flowering time in a ABA-dependent manner (Riboni et al, 2016), and more recently was shown to modulate transcription of nine-cis-epoxycarotenoid dioxygenase 3 (NCED3), a rate-limiting enzyme in ABA biosynthesis, a mechanism by which diurnal stomatal movement could be modulated (Baek et al, 2020).…”
Section: Resultsmentioning
confidence: 99%